Perceived Leadership Communication, Interpersonal Justice, and Job Performance: The Mediating Role of Trust in Leader - Mise Audina; Asep Gunawan; Risdianto Risdianto (Greenation International Journal of Tourism and Management, 2026)
The variable order fulfillment accuracy of an iron and steel industry illustrates the difficulties in sustaining employee performance under a challenging work environment. This study, grounded in social exchange theory, investigates the impact of perceived leadership communication and interpersonal justice on work performance, with trust in the leader serving as a mediating variable. A quantitative methodology was utilized, employing census sampling with a cohort of 150 employees. Data were examined utilizing structural equation modeling. The findings demonstrate that perceived leadership communication substantially influences work performance and trust in the leader. Trust in leadership significantly influences work performance and mediates the link between perceived leadership communication and job performance. Nonetheless, interpersonal justice does not substantially influence work performance or trust in leadership, whether directly or indirectly. The findings indicate that effective leadership communication cultivates employee trust, thereby improving work performance. Consequently, firms want to enhance leadership communication strategies to foster trust and elevate employee performance inside the manufacturing industry.